(untitled) (Olhar de Professor, 2022)
In this text, we report the experience with the artistic proposal "Living and sounding city of the land of Guairacá", carried out with 5th grade students from a municipal school and presented at the IV Art/Education Biennial of the Municipal Department of Education of Curitiba in the second half of 2019. The main objective of the proposal was to articulate the theme established by the Biennial - "Art and Life: open borders" - with the content taught in other curriculum components, such as history and geography. We imagined the possibility of starting from the reality lived by the students to poetically act across borders not only geographic (city of Curitiba), but temporal (19th century), with the creation and capture of soundscapes produced by the students, using different sound materials, later edited, whose result is characterized as a contemporary music composition, relying especially on Schafer (1991 and 2001), Zagonel (1999 and 2007), Torres and Kozel (2019).